Liver and diabetes. A vicious circle. Issue 1 (18th January 2013) - Loria, Paola; Lonardo, Amedeo; Anania, Frank
<x xml:space="preserve">Abstract</x> The complex and bi‐directional relationship linking the liver and diabetes has recently gained intense new interest. This critical review of the published work aims to highlight the most recent basic and clinical data underlying the development of type 2 diabetes, in those with non‐alcoholic fatty liver disease. Moreover, the potentially detrimental effects of type 2 diabetes in liver injury are also discussed in each of the two sections of the present paper. Fatty liver and diabetes share insulin resistance as their chief pathogenic determinant. The roles of the hypothalamus, the intestinal microbiome, white adipose tissue and inflammation are discussed in detail. Molecular insights into hepatocyte insulin resistance as the initiator of systemic insulin resistance are also presented with full coverage of the danger of fatty acids. Lipotoxicity, apoptosis, lipoautophagy, endoplasmic reticular stress response and recent developments in genetics are discussed. Closing the circle, special emphasis is given to biochemical pathways and clinical evidence supporting the role of type 2 diabetes as a risk factor for the development of progressive liver disease, including non‐alcoholic steatohepatitis, cirrhosis and primary liver cancer. In conclusion, data support non‐alcoholic fatty liver disease as a risk factor for the development of type 2 diabetes which is, in turn, a major contributor to progressive liver disease. This pathway leading from fatty liver to type 2 diabetes and back from the latter to the progressive liver disease is a vicious circle.